The Web server handbook - Palmer, Pete, 1961-.; Schneider, Adam.; Chenette, Anne. (Upper Saddle River, N.J. : Prentice Hall PTR, 1996)
The Internet and the World Wide Web; Overview of the World Wide Web; Why you should create a Web server; Quick start guide to the Internet and the Web; Web server fundamentals;; Connecting to the Internet; Setting up a Unix web server; Setting up a Windows web server; Setting up a Macintosh web server; How to create spiffy web pages; Publicizing your World Wide Web site; Running CGI programs on your Web server; A bunch of Perl Scripts; Web server security and maintenance.
"For Windows, NT, Macintosh, Linux, Unix systems, step-by-step instructions for creating a server, covers CGI and includes PERL, HTML, and UNIX quick references"--Cover.
Includes index.
Keywords: Computers; Web servers